2010
DOI: 10.1007/s13213-010-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of high-yield colonies of Rhizopus oryzae for enhanced production of fumaric acid

Abstract: Fumaric acid is an important four-carbon dicarboxylic acid as a potential biorefinery target. A highthroughput screening method for fumaric acid overproduction strains was established. Nystatin (50 mg/L) was added into the production medium to restrict the spread of Rhizopus oryzae hyphae on agar plates. With bromocerol green as a pH indicator in the agar plates, the capability of fumaric acid biosynthesis by single colony was positively correlated with the diameter ratio of the colored ring and the colony. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Studies conducted by our research group indicate that the ethanol production rate decreases significantly over time compared with the FA production rate, resulting in an increase in the FA yield over time [15]. This phenomenon is also present in the data of other authors [3,12,18,19], but has not been reported on. Manipulating the production phase to increase the fermentation time could lead to significant gains in FA yield.…”
Section: Introductionsupporting
confidence: 58%
“…Studies conducted by our research group indicate that the ethanol production rate decreases significantly over time compared with the FA production rate, resulting in an increase in the FA yield over time [15]. This phenomenon is also present in the data of other authors [3,12,18,19], but has not been reported on. Manipulating the production phase to increase the fermentation time could lead to significant gains in FA yield.…”
Section: Introductionsupporting
confidence: 58%
“…Developing high performance production strains is another use for directed evolution techniques, combining random mutagenesis using UV radiation with high-throughput screening techniques: a strain able to produce 160% more fumaric acid than the wild type strain has been chosen [41].…”
Section: Directed Evolutionmentioning
confidence: 99%
“…The lack of a powerful and versatile genetic toolbox for Rhizopus species has restricted wider biotechnological exploitation of this fungus. In previous studies on strain improvement, researchers have altered strains by mutagenesis using ultraviolet radiation or nitrosoguanidine treatment [ 2 , 13 15 ]. The first attempt to modify the biosynthetic pathway of fumaric acid in R. oryzae by metabolic engineering was in 2012 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%